Telaah Pemikiran Quraish Shihab dengan Tafsir Al-Misbah Surah Al-Alaq Ayat 1-5 dalam Pendidikan Islam di Keluarga - Lorens, Xena; Razzaq, Abdur; Imron, Kristina (LPPM Institut Pendidikan Nusantara Global, 2024)
This study aims to examine Quraish Shihab's thoughts on Islamic education in the family in the Tafsir Al-Misbah of Surah Al-Alaq verses 1-5 through Quraish Shihab's thoughts on Islamic education in the family in Surah Al-'Alaq verses 1-5 emphasizing the importance of reading, learning, and knowledge as a basis for character and moral formation in education. Quraish Shihab, through his interpretation, emphasizes the role of the family as the first and foremost educational institution in instilling religious and intellectual values. This study uses qualitative methods and the type of research used in is library research. With a descriptive-analytical approach to examine the interpretation and its relationship to education in the family. The results of the study indicate that Quraish Shihab's thoughts in the Tafsir Al-Misbah provide relevant guidance for the development of education based on Islamic values in the family, especially in the spiritual, intellectual, and moral development of children. So in this article it can be concluded that the role of the family as the first educational institution is highly emphasized, where parents are expected to be able to instill religious, spiritual, and intellectual values in children from an early age starting by teaching children to read and introducing Allah through the source of the Qur'an. This interpretation is relevant in the context of modern education to strengthen religious values and moral integrity in the family.